The implementation of occupational specific dispensation at a public hospital in Limpopo Province, South Africa: Professional nurses’ perspective. - Mothiba, T. M. (My University, 2014)
The aim of the study was to determine the perceptions of professional nurses regarding the implementation of Occupational Specific Dispensation (OSD) at public hospital in Limpopo province. A qualitative, descriptive, exploratory and contextual design was used. The population included all professional nurses who are working at the public hospital in Limpopo Province. A non-probability purposive sampling method was used to select the participants. Fourteen participants were included in the individual in-depth, unstructured interview sessions until data saturation was reached. Data were analyzed qualitatively by means of the Tesch’s open-coding method. Findings revealed one theme and seven sub-themes, namely; Meetings prior OSD implementation, OSD in identified special units, Frustrations based on OSD implementation, Advantages of OSD implementation, OSD for professional nurses, Job dissatisfaction related to OSD implementation and Interpersonal relationship after implementation of OSD. The study recommends that there is a need to improve the salary of the employees, and the Department of Health (DoH) should make sure that the professional nurses are informed about the implementation process of OSD.
Mothiba, T.M. (2014). The implementation of occupational specific dispensation at a public hospital in Limpopo Province, South Africa: Professional nurses’ perspective. African Journal for Physical, Health Education, Recreation and Dance, June (Supplement 1:2), 448-456.
Keywords: Professional nurses; Occupation Specific Dispensation; University hospitals; Public hospitals; Nurses -- South Africa